The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1213/01.ane.0000237415.18715.1d
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Oral Carbohydrate Administration to ASA III-IV Patients Undergoing Elective Cardiac Surgery

Abstract: In this study we investigated the effects of preoperative oral carbohydrate administration on postoperative insulin resistance (PIR), gastric fluid volume, preoperative discomfort, and variables of organ dysfunction in ASA physical status III-IV patients undergoing elective cardiac surgery, including those with noninsulin-dependent Type-2 diabetes mellitus. Before surgery, 188 patients were randomized to receive a clear 12.5% carbohydrate drink (CHO), flavored water (placebo), or to fast overnight (control). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
1
20

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(131 citation statements)
references
References 27 publications
5
100
1
20
Order By: Relevance
“…To this end, the concept of “fast‐track surgery” was introduced in the 1990s by Henrik Kehlet. It was demonstrated that by applying evidence‐based perioperative principles to open colonic surgery, the post‐operative length of hospital stay could be reduced to 2–3 days 1, 2. Realising that the surgical journey involves many professional competencies, a more integrated, multiprofessional, multidisciplinary approach was needed, whereby a decision taken early in the course of the treatment plan would impact on later developments and influence the choices available for recovery further down the line.…”
Section: Figurementioning
confidence: 99%
“…To this end, the concept of “fast‐track surgery” was introduced in the 1990s by Henrik Kehlet. It was demonstrated that by applying evidence‐based perioperative principles to open colonic surgery, the post‐operative length of hospital stay could be reduced to 2–3 days 1, 2. Realising that the surgical journey involves many professional competencies, a more integrated, multiprofessional, multidisciplinary approach was needed, whereby a decision taken early in the course of the treatment plan would impact on later developments and influence the choices available for recovery further down the line.…”
Section: Figurementioning
confidence: 99%
“…16 Kli nik ça lış ma lar da; pre o pe ra tif 2-3 sa at ön ce su ve ya karbonhidrat tan zen gin sı vı alı mı nın susuz luk ve ağız ku ru lu ğu his si ni, karbonhidrat tan zen gin sı vı alı mı nın ay rı ca aç lık his si ni de azalt tı ğı sap tan mış tır. 8,9,[21][22][23] Ha u sel ve ark. la pa ros ko pik kole sis tek to mi ve ya ko lo rek tal cer ra hi ge çi re cek hasta lar da pre o pe ra tif dö nem de oral karbonhidrat tan zen gin sı vı ve ya su içil me si nin su suz luk his si ni, oral kar bon hid rat tan zen gin sı vı içil me si nin ise aynı zan man da aç lık, hal siz lik his si ve bun la ra bağ lı ank si ye te yi azalt tı ğı nı ile ri sür müş ler dir.…”
Section: Tar Tiş Maunclassified
“…Recent studies investigating preoperative oral carbohydrate loading in CABG patients have shown no improvement in insulin sensitivity postoperatively (73,74). However, these studies were limited as they infered insulin sensitivity only from the insulin requirements needed to maintain blood glucose at ≤10 (72) or between 4 to 7 mmol/L (73). This approach is not a generally accepted measure of insulin sensitivity and has not been related to the gold standard hyperinsulinemic euglycemic clamp technique.…”
Section: Discussionmentioning
confidence: 99%
“…Not all studies have had similar findings. A study conducted by Breuer et al (2006) investigated the effects of a preoperative carbohydrate drink on insulin resistance in CABG and valve replacement surgical patients (72). Glucose levels and insulin requirements to maintain blood glucose levels at ≤10.0 mmol/L postoperatively did not differ among the treatment, placebo or fasted group, suggesting that the carbohydrate drink did not provide any benefit in reducing insulin resistance.…”
Section: Oral Preoperative Carbohydrates and Insulin Resistancementioning
confidence: 99%